Fibroblast activation protein-based theranostics in pancreatic cancer - Cheng, Chien-shan; Yang, Pei-wen; Sun, Yun; Song, Shao-li; Chen, Zhen (Frontiers in Oncology, 2022)
Fibroblast activation protein-α (FAP) is a type II transmembrane serine protease that has specific endopeptidase activity. Given its well-established selective expression in the activated stromal fibroblasts of epithelial cancers, although not in quiescent fibroblasts, FAP has received substantial research attention as a diagnostic marker and therapeutic target. Pancreatic cancer is characterized by an abundant fibrotic or desmoplastic stroma, leading to rapid progression, therapeutic resistance, and poor clinical outcomes. Numerous studies have revealed that the abundant expression of FAP in cancer cells, circulating tumor cells, stromal cells, and cancer-associated fibroblasts (CAFs) of pancreatic adenocarcinoma is implicated in diverse cancer-related signaling pathways, contributing to cancer progression, invasion, migration, metastasis, immunosuppression, and resistance to treatment. In this article, we aim to systematically review the recent advances in research on FAP in pancreatic adenocarcinoma, including its utility as a diagnostic marker, therapeutic potential, and correlation with prognosis. We also describe the functional role of FAP-overexpressing stromal cells, particulary CAFs, in tumor immuno- and metabolic microenvironments, and summarize the mechanisms underlying the contribution of FAP-overexpressing CAFs in pancreatic cancer progression and treatment resistance. Furthermore, we discuss whether targeting FAP-overexpressing CAFs could represent a potential therapeutic strategy and describe the development of FAP-targeted probes for diagnostic imaging. Finally, we assess the emerging basic and clinical studies regarding the bench-to-bedside translation of FAP in pancreatic cancer.